Pengenalan Phbs Dengan Metode Edukasi Interaktif Untuk Membentuk Budaya Sekolah Sehat Pada Anak Tk An Namiroh - Dewinny Septalia Dale; Dwi Sapta Aryantiningsih; Cinthia Maharani; Bintang Kumala Sari; Melisa Raja Gukguk; Mery Melinda Pane; Shella Hilwani Putri; Shintya Rahmayuni; Sintiya Awaliyah; Siska Br Torus (CV. ITTC INDONESIA, 2026)
Clean and Healthy Living Behaviors (PHBS) in early childhood need to be habituated through developmentally appropriate learning strategies so they become part of daily school routines. This article aims to describe the effectiveness of introducing PHBS through interactive education to foster a healthy school culture among children at TK AN Namiroh. The program applied a participatory educational approach through interactive counseling, demonstration, and hands-on practice simulations. The participants were 22 children in one class. Implementation consisted of one day of interactive education, followed by one day of classroom habituation led by the homeroom teacher, and a direct evaluation using an observation checklist of PHBS behaviors. The observation results indicated that 20 children reached the “able and understand” category in applying the trained PHBS behaviors, while 2 children were still adjusting and required additional reinforcement for step consistency and independence. These findings suggest that interactive education combined with short-term habituation and performance-based assessment can establish observable PHBS practices in the classroom and provide a practical basis for positioning PHBS as a measurable routine within a healthy school culture.